SUCCESSIVELY OFF-PUMP CORONARY ARTERY BYPASS GRAFTING AND CAROTID STENTING IN A PATIENT WITH AN ASYMPTOMATIC CAROTID LESION - Vladimir Kornovski; Andrey Andreev (Peytchinski Publishing, 2021)
The case we are presenting is 70 years male with triple vessel coronary artery disease in combination with a unilateral asymptomatic carotid lesion of A. Carotis communis dextra. He underwent off-pump coronary artery bypass grafting (OPCAB) subsequently right carotid stenting with an excellent outcome.